Evaluation of lipid damage related to pathological and physiological conditions. (July 2013) - Garcia, Solange Cristina; Grotto, Denise; Bulcão, Rachel Picada; Moro, Angela Maria; Roehrs, Miguel; Valentini, Juliana; de Freitas, Fernando Araújo; Paniz, Clovis; Bubols, Guilherme Borges; Charão, Mariele Feiffer
<x xml:space="preserve">Abstract</x> Several diseases and xenobiotics are known to generate reactive species that may trigger oxidative stress when not properly scavenged by the antioxidant defenses and result in tissue damage. We investigated lipid peroxidation (LPO) as a possible mechanism for tissue damage in some pathologies, in the normal aging process, and in subjects exposed to organic solvents. Plasmatic malondialdehyde (MDA) was quantified by high-performance liquid chromatography with visible wavelength detection in 239 subjects and divided into the following: acute myocardium infarction (AMI), diabetes without complications (D) and hemodialysis (HD) patients; into healthy children, adults, and elderly, all nonexposed to xenobiotics; and into painters occupationally exposed to organic solvents (P). Troponin, glycated hemoglobin, and transminases [aspartate aminotransferase (AST) and alanine aminotransferase] were analyzed. An increase in LPO was observed in AMI, D, HD, and P groups, when compared to healthy adults. No correlation between MDA and age was found. Further, we found positive correlations between MDA versus troponin (r = 0.47), MDA versus HbA1c (r = 0.56), and MDA versus AST (r = 0.41) in AMI, diabetics, and painters, respectively. This work has demonstrated increased lipid and protein damages in myocardium and blood, along with an alteration of hepatic transaminase activities and induction of LPO, suggesting that MDA levels are important to evaluate the extent of tissue alterations and development of acute and chronic conditions.